2010
DOI: 10.1007/s11099-010-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in unsaturated fatty acids in membrane lipids of Suaeda salsa L. enhances protection of photosystem II under high salinity

et al.

Abstract: In order to examine the possible role of unsaturated fatty acids in photosynthesis of halophytes under high salinity, the effect of salinity on plant growth, chlorophyll (Chl) content, photochemical efficiency of PSII, membrane lipid content and fatty acids composition of a C 3 euhalophyte Suaeda salsa L. was investigated. Salt stress induced a slight increase of the maximal photochemical efficiency of PSII (F v /F m ), actual PSII efficiency (Φ PSII ), Chl a content and Chl a/b ratio. The unsaturated fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 37 publications
7
82
0
1
Order By: Relevance
“…Numerous studies have shown that salinity stress predisposes photosystem II (PSII) to photoinhibitory damage (Lu et al 2002;Maricle et al 2007;Hichem et al 2009;Qin et al 2010Qin et al , 2011Sui et al 2010). However, very little attention has been paid to the responses of PSII to salinity stress and high-temperature stress in combination (Henley et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that salinity stress predisposes photosystem II (PSII) to photoinhibitory damage (Lu et al 2002;Maricle et al 2007;Hichem et al 2009;Qin et al 2010Qin et al , 2011Sui et al 2010). However, very little attention has been paid to the responses of PSII to salinity stress and high-temperature stress in combination (Henley et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of NaCl increased 50 mM every day until it reached a final concentration. Measuring physiological indexes after treated with NaCl for 5 days (Sui et al, 2010).…”
Section: Plant Cultivation and Treatmentmentioning
confidence: 99%
“…For quantitative analysis, lipids were separated by TLC. The individual lipids was then measured by gas chromatography (GC-9A, Shimadzu, Japan) as described by Sui et al (2010).…”
Section: Lipid Extraction and Analysismentioning
confidence: 99%
See 2 more Smart Citations